Copy number variations residing outside the SHOX enhancer region are involved in Short Stature and Léri‐Weill dyschondrosteosis. Issue 1 (23rd November 2021) - Fanelli, Antonella; Vannelli, Silvia; Babu, Deepak; Mellone, Simona; Cucci, Alessia; Monzani, Alice; Al Essa, Wael; Secco, Andrea; Follenzi, Antonia; Bellone, Simonetta; Prodam, Flavia; Giordano, Mara
Abstract: Background: SHOX enhancer CNVs, affecting one or more of the seven recognized evolutionary conserved non‐coding elements (CNEs) represent one of the most frequent cause of SHOX ‐haploinsufficiency. During the diagnostic workflow deletions/duplications have been identified downstream SHOX not including any of the these CNEs. Methods: Fine tiling aCGH and breakpoint PCR were used to characterize the critical interval and to search for novel alterations in a cohort of selected patients. Results: Screening of 252 controls provided evidence that duplications in this area represent likely benign variants whereas none of the deletions were detected. These findings suggested that other alterations relevant for SHOX ‐haploinsufficiency might be missed by the standard diagnostic methods. To identify such undisclosed elements, the aCGH was used to reanalyze 52 unresolved cases with clinical features strongly suggestive of SHOX ‐haploinsufficiency. This analysis followed by the screening of 210 patients detected two partially overlapping small deletions of 12 and 8 kb in four unrelated individuals, approximately 15 kb downstream SHOX, that were absent in 720 normal stature individuals. Conclusion: Our results strengthen the hypothesis that alterations of yet unidentified cis‐regulatory elements residing outside those investigated through conventional methods, might explain the phenotype in ISS/LWD patients thus enlarging the spectrum of variants contributing to SHOX ‐haploinsufficiency. Abstract : The characterization of deletions identified in Short Staure patients through fine tiling aCGH narrowed down a critical interval downstream the enhancer that might contains elements relevant for SHOX expression. To identify undisclosed